Noción de sujeto suicida que manejan los profesionales del área de la salud mental - Escobar Campos, Angie Paola (Universidad de San Buenaventura - Cali, 2017)
Objective. Describe the meanings that manage professionals in health and influence on the intervention or approach to suicidal patients. Method. Descriptive, qualitative and interpretative, based on interviews, projective tests, applied to three subjects Cali, Professional Nursing, Psychology and Psychiatry. Results. In the representations rescue the use of beliefs and emotional support, awareness about the scale of current values, in addition to the concealment of depression. According to the experiences the intervention is understood as an inter-space as well as the importance of developing a differentiated approach and work experience as a factor in the treatment of patients. And as conceptual frameworks, professionals have two pathological medical and other social perspectives to conceptualize the phenomenon, its disciplines take different paths to mitigate risks and awareness of professional ethics. Conclusions. Professionals perceive they are not sure to where their efforts can help mitigate the problems, the future seems uncertain but professionals still gather knowledge to improve their intervention, correct errors and reconsider its position as a subject that plays a role professional.